1999
DOI: 10.1007/s002130050910
|View full text |Cite
|
Sign up to set email alerts
|

5-HT 2C receptors are involved in the discriminative stimulus effects of citalopram in rats

Abstract: Rats were trained on a fixed ratio 10, food-reinforced schedule to recognize a discriminative stimulus (DS) elicited by the selective serotonin (5-HT) reuptake inhibitor (SSRI), citalopram (2.5 mg/kg, IP). The preferential, high efficacy agonist at 5-HT2C receptors, Ro60-0175, dose-dependently generalized to citalopram with an ED50 of 0.3 mg/kg, IP. Further, the selective 5-HT2C receptor antagonist, SB242,084, dose-dependently (ED50=0.1 mg/kg, IP) blocked the citalopram DS. These data suggest that 5-HT2C recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…Thus, the facilitatory influence of SB242,084 on citalopram-induced LA in this novel environment might also involve relief of its anxiogenic properties. Indeed, 5-HT 2C receptors are of special interest in light of their broad implication in the actions of SSRIs (Millan et al 1999b). In analogy to LA, antidepressant actions of SSRIs were enhanced by 5-HT 2C antagonists in certain studies (Yamada and Sugimoto 2001), though other authors reported their attenuation (Clemett et al 2001).…”
Section: -Ht 2c Receptorsmentioning
confidence: 97%
“…Thus, the facilitatory influence of SB242,084 on citalopram-induced LA in this novel environment might also involve relief of its anxiogenic properties. Indeed, 5-HT 2C receptors are of special interest in light of their broad implication in the actions of SSRIs (Millan et al 1999b). In analogy to LA, antidepressant actions of SSRIs were enhanced by 5-HT 2C antagonists in certain studies (Yamada and Sugimoto 2001), though other authors reported their attenuation (Clemett et al 2001).…”
Section: -Ht 2c Receptorsmentioning
confidence: 97%
“…Although additional subtypes (5-HT6 and 5-HT7) certainly exist, 23) studies have revealed the presence of at least four types of 5-HT receptors in the spinal cord (5-HT1, 5-HT2, 5-HT3 and 5-HT4) with several subtypes. 24,25) The use of relatively selective agonists and antagonists at the recently described 5-HT receptor subtypes has brought to light a complex picture of the roles of these receptors in that spinal administration can produce both pro-and antinociceptive effects. In the tail-flick test, intrathecally administered 5-HT1 A antagonists do not alter 26) or produce a dose-related blockade 27) of 5-HT-induced antinociception.…”
Section: )mentioning
confidence: 99%
“…13 C-NMR (CDCl 3 , 75.5 MHz) d: 17.7 (C-8Ј), 17.9 (C-5Љ), 22.0 (C-3Ј), 22.6 (C-7Ј), 25.6 (C-4Љ), 25.7 (C-6Ј), 28.3 (C-1Љ), 29.9 (C-3), 37.1 (C-2Ј), 73.8 (C-1Ј), 89.6 (C-2), 121.4 (C-2Љ), 121.8 (C-5), 123.1 (C-3a), 124.0 (C-4Ј), 125.0 (C-6), 127.2 (C-7), 131.4 (C-4), 132.2 (C-5Ј), 133.2 (C-3Љ), 162.4 (C-7a), 171.7 (C8).…”
mentioning
confidence: 99%
“…Although it cannot be formally excluded that other actions of mirtazapine and mianserin might be involved (Broekkamp et al 1995), these observations support the argument that a similar mechanism is implicated in the present effects, that is, blockade of 5-HT 2C receptors. This argument is underpinned by the finding that the highly selective 5-HT 2C antagonist, SB242,084, likewise blocks the DS properties of both RO60,0175 and citalopram (Dekeyne et al 1999;Millan et al 1999a).…”
Section: Discussionmentioning
confidence: 93%